Pharmacodynamic properties of essential oils from Cymbopogon species - Mohd Fazrullah Innsan M.F.; Shahril M.H.; Samihah M.S.; Asma O.S.; Abd Jalil A.K.; Salina Mat Radzi; Hanina Mohd Noor (2024)
Indexed by Scopus/WOS